Basin scale survey of marine humic fluorescence in the Atlantic: Relationship to iron solubility and H2O2. Issue 1 (14th February 2013) - Heller, M. I.; Gaiero, D. M.; Croot, P. L.
<x xml:space="preserve">Abstract</x> [1] Iron (Fe) is a limiting nutrient for phytoplankton productivity in many different oceanic regions. A critical aspect underlying iron limitation is its low solubility in seawater as this controls the distribution and transport of iron through the ocean. Processes which enhance the solubility of iron in seawater, either through redox reactions or organic complexation, are central to understanding the biogeochemical cycling of iron. In this work we combined iron solubility measurements with parallel factor (PARAFAC) data analysis of Coloured Dissolved Organic Matter (CDOM) fluorescence along a meridional transect through the Atlantic (PS ANT XXVI‐4) to examine the hypothesis that marine humic fluorescence is a potential proxy for iron solubility in the surface ocean. PARAFAC analysis revealed 4 components (C1‐4), two humic like substances (C2&4) and two protein‐like (C1&3). Overall none of the 4 components were significantly correlated with iron solubility, though humic‐like components were weakly correlated with iron solubility in iron replete waters. Our analysis suggests that the ligands responsible for maintaining iron in solution in the euphotic zone are sourced from both remineralisation processes and specific ligands produced in response to iron stress and are not easily related to bulk CDOM properties. The humic fluorescence signal was sharply attenuated in surface waters presumably most likely due to photo bleaching, though there was only a weak correlation with the transient photo product H2O2, suggesting longer lifetimes in the photic zone for the fluorescent components identified here.